Chloramphenicol treatment for acute infective conjunctivitis in children in primary care: a randomised double-blind placebo-controlled trial. - Rose, P; Harnden, A; Brueggemann, A; Perera, R; Sheikh, A; Crook, D; Mant, D (2005)
BACKGROUND: One in eight schoolchildren have an episode of acute infective conjunctivitis every year. Standard clinical practice is to prescribe a topical antibiotic, although the evidence to support this practice is scarce. We undertook a randomised double-blind trial to compare the effectiveness of chloramphenicol eye drops with placebo in children with infective conjunctivitis in primary care. METHODS: Our study included 326 children aged 6 months to 12 years with a clinical diagnosis of conjunctivitis who were recruited from 12 general medical practices in the UK. We assigned 163 children to receive chloramphenicol eye drops and 163 to receive placebo eye drops. Eye swabs were taken for bacterial and viral analysis. The primary outcome was clinical cure at day 7, which was assessed from diaries completed by parents. All children were followed up for 6 weeks to identify relapse. Survival statistics were used for comparison, and analysis was by intention to treat. FINDINGS: Nine children were lost to follow-up (one in chloramphenicol group; eight in placebo group). Clinical cure by day 7 occurred in 128 (83%) of 155 children with placebo compared with 140 (86%) of 162 with chloramphenicol (risk difference 3.8%, 95% CI -4.1% to 11.8%). Seven (4%) children with chloramphenicol and five (3%) with placebo had further conjunctivitis episodes within 6 weeks (1.2%, -2.9% to 5.3%). Adverse events were rare and evenly distributed between each group. INTERPRETATION: Most children presenting with acute infective conjunctivitis in primary care will get better by themselves and do not need treatment with an antibiotic.